1996
DOI: 10.1149/1.1837322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mechanical Grinding on the Lithium Intercalation Process in Graphites and Soft Carbons

Abstract: The effects of mechanical grinding on morphology and electrochemical performance of graphite and soft carbon powders with respect to lithium insertion were studied. The morphology of the milled graphitic powders was found to depend strongly upon the nature of the interactions (e.g., impact or shear) generated by the two kinds of mixer mills used. For the same milling time, crystallite size was smallest and the density of defects highest for graphitic powders that were ballmilled using impact interactions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(114 citation statements)
references
References 3 publications
(4 reference statements)
6
100
1
Order By: Relevance
“…The irreversible capacity in the first cycle is considered coming from the formation of a passivating film, which consumes lithium at the electrode materials/electrolyte interface. [21][22][23] From SEM observation, we found that the spherical MCMB particles were severely damaged after 20 h ballmilling. Therefore, the sample F ͑ballmilled for 20 h͒ anode exhibited a very high irreversible capacity.…”
Section: Resultsmentioning
confidence: 99%
“…The irreversible capacity in the first cycle is considered coming from the formation of a passivating film, which consumes lithium at the electrode materials/electrolyte interface. [21][22][23] From SEM observation, we found that the spherical MCMB particles were severely damaged after 20 h ballmilling. Therefore, the sample F ͑ballmilled for 20 h͒ anode exhibited a very high irreversible capacity.…”
Section: Resultsmentioning
confidence: 99%
“…In order to achieve lithium intercalation, a milling process has been performed in graphite and soft carbons. 211,212 The effects of milling on the morphology and electrochemical performance of graphite and soft carbon powders with respect to lithium insertion were studied. The morphology of the milled graphite powders was found to depend strongly upon the nature of the interactions (i.e.…”
Section: Elements and Alloysmentioning
confidence: 99%
“…These characteristics related to ball-milled graphites have been previously reported. [7][8][9][10][11][12] A noticeable feature noted from the XRD patterns in Figure 3(b) and (c) is that in the case of argon milled sample the (002) diffraction peak of graphite recovers after annealing at temperatures above 1000 o C, while for air milled graphite, the XRD profile near the (002) peak position of graphite appears to be similar before and after annealing. This means that the disordered structure of ballmilled graphite is more stabilized by milling under air atmosphere than under argon.…”
Section: Resultsmentioning
confidence: 84%
“…[7][8][9][10][11][12] However, ballmilled graphites exhibit a large irreversible capacity loss during the first charge (intercalation) due to their large specific surface areas. [7][8][9] To solve the problem, encapsulating the ball-milled graphite particles with a soft carbon is an effective method, making them less susceptible to irreversible reactions. On the other hand, the structure and properties of ball-milled graphite is significantly influenced by the atmosphere during ball-milling.…”
Section: Introductionmentioning
confidence: 99%